2019
DOI: 10.13005/ojc/350502
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Source Identification of Halda River Water Using Field Observation, Laboratory Analysis and GIS Technique

Abstract: Halda River (HR), the lone natural carp breeding ground in Bangladesh as well as in Southeast Asia is an economically important river and its water quality is deteriorating due to unplanned industrialization and various anthropogenic activities. The present research work has been conducted to assess the characteristics of HR water. Eighteen water quality parameters were studied including pH, temperature, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Dissolved Solids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The WHO standard value is also reported as 1,000 μScm −1 (WHO, 1993b). Our results of EC were found (Table 1) within the permissible limit (Ahmed et al, 2010;Bhuyan & Bakar, 2017;Karim et al, 2019;Patra & Azadi, 1985). In addition the EC value was reported in Karnaphuli River (Dey et al, 2017) which is a matter of concern as the Karnaphuli River water intrudes into the Halda River.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The WHO standard value is also reported as 1,000 μScm −1 (WHO, 1993b). Our results of EC were found (Table 1) within the permissible limit (Ahmed et al, 2010;Bhuyan & Bakar, 2017;Karim et al, 2019;Patra & Azadi, 1985). In addition the EC value was reported in Karnaphuli River (Dey et al, 2017) which is a matter of concern as the Karnaphuli River water intrudes into the Halda River.…”
Section: Discussionsupporting
confidence: 79%
“…Due to the increased amount of suspended solids, the Total Solids (TS) of the river was also higher than ever before and the average TS value of the Halda River water in the sampling months at different sampling points ranged from 1,590.07 to 2,952.4 mgL −1 , which is a sign of pollution (Islam et al, 2016; Sarwar et al, 2010). Moreover, the present study revealed that the average results of turbidity of water samples indicates that the Halda River water was highly turbid than the permissible limit (5 –25 NTU) (Karim et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…Halda, Bakkhali, Sangu, Matamuhuri, Naf, Kasalong and Chingri River was found to be affected by anthropogenic activity (Tables 1 , 2 , and 3 ) [ 126 , 132 , 133 , 134 , 135 ]. Dissolve oxygen (DO) concentrations was found <4 in Halda River [ 126 , 132 ].…”
Section: River Pollution In Bangladeshmentioning
confidence: 99%
“…They added that the Halda River's lower pH (6.2-6.8) encourages carp species to spawn. According to Karim et al [55], the pH range of the Halda River's water is 7.08 to 7.65, and it is usually alkaline. They added that minor pH fluctuations did not affect fish habitat.…”
Section: Discussionmentioning
confidence: 99%